Business analysis of competitors prices for new products - Klymentova, Marija; Kobielieva, T. O. (My University, 2023)
Business analysis of competitor prices for new products is a method of checking the competitiveness of one's own products or services, which is carried out on the basis of data from monitoring competitors' prices and the dynamics of their changes on the market, since with a decrease in the price of the same product on other trading platforms, potential customers can choose exactly those stores where it is more profitable for them to buy.
Бізнес-аналіз цін конкурентів на нові продукти
Keywords: market; competition; price policy; formation of models; production